2012
DOI: 10.1016/j.freeradbiomed.2012.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA damage Is associated with reduced mitochondrial bioenergetics in Huntington's disease

Abstract: Oxidative stress and mitochondrial dysfunction have been implicated in the pathology of HD, however the precise mechanisms by which mutant huntingtin modulates levels of oxidative damage in turn resulting in mitochondrial dysfunction are not known. We hypothesize that mutant huntingtin increases oxidative mtDNA damage leading to mitochondrial dysfunction. We measured nuclear and mitochondrial DNA lesions and mitochondrial bioenergetics in the STHdhQ7 and STHdhQ111 in vitro striatal model of HD. Striatal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 77 publications
2
92
0
1
Order By: Relevance
“…The mitochondrial dysfunction pathway has 37 DEGs, while there are 42 DEGs in the Huntington's disease signaling pathway. Mitochondrial dysfunction is believed to play a role in Huntington's disease pathology, and prior studies have demonstrated that APE1 is important for the maintenance of mitochondrial function (Li et al ., 2012; Siddiqui et al ., 2012). APE1 is also known to participate in mitochondrial DNA repair functions (Ballista‐Hernandez et al ., 2017; Stuart et al ., 2004; Vascotto et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial dysfunction pathway has 37 DEGs, while there are 42 DEGs in the Huntington's disease signaling pathway. Mitochondrial dysfunction is believed to play a role in Huntington's disease pathology, and prior studies have demonstrated that APE1 is important for the maintenance of mitochondrial function (Li et al ., 2012; Siddiqui et al ., 2012). APE1 is also known to participate in mitochondrial DNA repair functions (Ballista‐Hernandez et al ., 2017; Stuart et al ., 2004; Vascotto et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…One previously linked pathway of particular interest is the mitochondrial dysfunction pathway. APE1 redox and repair activity has previously been shown to be responsible for maintaining and repairing mitochondrial DNA (Ballista‐Hernandez et al ., 2017; Li et al ., 2012; Siddiqui et al ., 2012; Stuart et al ., 2004; Vascotto et al ., 2009). The results of our studies presented here identify, for the first time, the genes responsible for these functions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the striatum is highly susceptible to dysfunction of mitochondrial oxidative phosphorylation [92]. ROS formation in HD can further damage mitochondria by dissipating the mitochondrial membrane potential, dysregulating ATP production and leading to oxidation of mtDNA [8,23,93], which is highly vulnerable to oxidative damage due to its proximity to the respiratory chain, limited repair mechanisms, few non-coding sequences and lack of histones [94]. We have previously shown that O 2 x-formation also rises in HD human cybrids following exposure to 3-nitropropionic acid or staurosporine [43].…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of mitochondrial content and function in HD have demonstrated decreases in the protein content of electron transport chain complexes II & III, along with decreases in the activity of complexes II/III & IV (Mann et al, 1990;Gu et al, 1996;Browne et al, 1997). Decreased mitochondrial DNA (mtDNA) abundance has also been observed (Horton et al, 1995) along with increases in mtDNA lesion frequency (Siddiqui et al, 2012), indicating that the mitochondrial genome is damaged by mHtt. Further, support for a causative role of mitochondrial dysfunction in HD pathology comes from observations where exposure of healthy animals to the mitochondrial complex II inhibitor 3-nitropropionic acid (Brouillet et al, 1995) can also result in striatal degeneration and produce symptoms similar to those observed in animal models of HD.…”
Section: Introductionmentioning
confidence: 99%